His Dark Materials : The Golden Compass, The Subtle Knife, The Amber Spyglass - Books 1-3 - Pullman, Philip, 1946-; 1946-; Pullman, Philip, 1946-; Pullman, Philip, 1946- (New York : Alfred A. Knopf, 2011)
Includes the three works in Pullmans classic fantasy trilogy, which has often been considered a reimagining of Miltons Paradise lost.
Keywords: Belacqua, Lyra (Fictitious character) -- Juvenile fiction; Parry, Will (Fictitious character) -- Juvenile fiction; Imaginary places -- Juvenile fiction; Demonology -- Juvenile fiction; Witches -- Juvenile fiction; Missing persons -- Juvenile fiction; Kidnapping -- Juvenile fiction; Psychobiology, Experimental -- Juvenile fiction; Belacqua, Lyra (Fictitious character) -- Fiction; Parry, Will (Fictitious character) -- Fiction; Imaginary places -- Fiction; Demonology -- Fiction; Witches -- Fiction; Missing persons -- Fiction; Kidnapping -- Fiction; Psychobiology, Experimental -- Fiction; Fantasy